Manajemen Kesiswaan dalam Membentuk Karakter Religius Siswa - Syafi’i, Imam (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2023)
Student management has an important role in educational institutions, namely managing student activities so that these activities can run smoothly, in an orderly and regular manner to contribute to the achievement of madrasah goals and overall educational goals. Student management and religious character have a relationship, namely religious character must be instilled in students from an early age. In the process of forming students' religious character, it will not take place by itself, but the process is influenced by the school environment. This study used a descriptive qualitative research approach with field research using data collection techniques: 1) Observation 2) Interview 3) Documentation. There are two types of data validity in this study: 1) Source triangulation and 2) Technical triangulation. Data analysis in this study used the interactive model Milles, Huberman, and Saldana. This research concludes 1) Analysis and acceptance in shaping the religious character of students at MAN 2 Banyuwangi through learning in the classroom and outside the classroom. Then the recruitment process to build the religious character of students is through achievement and regular routes. Furthermore, the selection process carried out by the teacher is by conducting religious activities through the takmir of the At-Ta'awun mosque. 2) Orientation and placement in shaping the religious character of students at MAN 2 Banyuwangi on the academic aspect are in addition to class and department placement, namely by implementing a culture of obligatory Dhuha and Dhuhur prayers in congregation, Koran recitation activities before KBM, and other religious activities. While the non-academic aspect is through extracurricular activities, each extracurricular supervisor combines it with religion. 3) Guidance and development in shaping the religious character of students at MAN 2 Banyuwangi on the curricular aspect is through classroom learning and combining it with religion. Then on the co-curricular aspect is through the application of talents and interests, meaning that students of MAN 2 Banyuwangi are provided with facilities by Madrasas in the form of facilities and infrastructure for talent and interest activities to hone their potential so that students have quality abilities in the fields of imtaq and science and technology. Likewise in the extracurricular aspect, namely every teacher who becomes a coach combines it with religion.